PENGARUH GAYA KEPEMIMPINAN GEMBALA SIDANG DAN KESEJAHTERAAN TERHADAP MOTIVASI MELAYANI GURU SEKOLAH MINGGU DI GBI JAKARTA TIMUR - Ndolu, Yopie; Putrawan, Bobby Kurnia (SEKOLAH TINGGI TEOLOGI KIBAID MAKALE, 2021)
This study aims to determine the relationship between the pastor's leadership style and the welfare of serving on the motivation to serve Sunday school teachers in GBI sector 1, East Jakarta. The method used in this study is a correlational survey. The research sample was 35 people who were taken using a simple random sampling technique. The instrument used in collecting data was a questionnaire. The validity test used the Pearson Product Moment formula, and the reliability was analysed using the Alpha Cronbach formula. Based on testing the significance of the multiple correlation coefficient, the coefficient is 46.911 with a P-value of 0.000. Because the P-value is less than 0.05, it is very significant, then H0 is rejected, and H1 is accepted. It can be concluded that there is a positive and significant relationship between the leadership style of the pastor and the welfare of serving together with the motivation to serve with a multiple correlation coefficient (Ry.12) of 0.864. The coefficient of determination (R2y.12) is 0.730, which means that 73.00% of the variance in serving motivation can be explained by the pastor's leadership style and the welfare of performing together.